2017
DOI: 10.1007/s00167-017-4704-6
|View full text |Cite
|
Sign up to set email alerts
|

Discoid lateral meniscus can be overlooked by magnetic resonance imaging in patients with meniscal tears

Abstract: Level I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…We acknowledge that there are some limitations to our study. First, MRI was acted as the "gold standard" for DLM 21 , without further confirmation through arthroscopy. Second, we did not differentiate between complete and incomplete types of DLM.…”
Section: Limitationsmentioning
confidence: 99%
“…We acknowledge that there are some limitations to our study. First, MRI was acted as the "gold standard" for DLM 21 , without further confirmation through arthroscopy. Second, we did not differentiate between complete and incomplete types of DLM.…”
Section: Limitationsmentioning
confidence: 99%
“…Despite the results of Sohn et al. (29), the nature of meniscal tears was mostly oblique (15/31). Contrary to the studies of Bin (28) and Araki (26), MM tears with type I DLM had only an oblique pattern, whereas type II DLM cases had different tear patterns.…”
Section: Discussionmentioning
confidence: 82%
“…reported that MRI showed that 35 knees had radial tears (45%, 35/78) and 34 knees had horizontal tears (44%, 34/78) as solely or a component of combined meniscus tear in 78 knees with DLM. Radial tears were found to be the most common pattern of tears and horizontal tears were the second most common (29).…”
Section: Discussionmentioning
confidence: 99%
“…100,101 In addition, MRI has a certain diagnostic value in classification, tear type and location, and peripheral rim stability of DLM. 48,95,[102][103][104][105][106][107] The diagnostic specificity and sensitivity of MRI in adult DLM tears are 100% and 97.8%, 108 but in children's DLM and its lesions are still controversial. 47,109,110 In patients with unilateral symptomatic DLM, the probability of DLM in the contralateral knee is about 73%-97%, 6 and of the same type in both is 88%.…”
Section: Diagnostic Value Of Mri On Dlm and Its Classification Andmentioning
confidence: 99%